Managed care improves prognosis in acute myocardial infarction survivors. Data from the MAnaged Care for Acute Myocardial Infarction Survivors (MACAMIS) Programme. (25th November 2020) - Jankowski, P; Topor-Madry, R; Gasior, M; Ceglowska, U; Eysymontt, Z; Gierlotka, M; Wita, K; Legutko, J; Dudek, D; Sierpinski, R; Pinkas, J; Kazmierczak, J; et al.
Abstract: Background: Mortality following acute myocardial infarction (MI) remains high despite progress in pharmacotherapy and interventional treatment. In 2017 a nation-wide system of managed care for MI survivors comprising a continuum of acute treatment of MI, staged revascularization, cardiac rehabilitation, cardiac electrotherapy and cardiac ambulatory care within one year following MI was implemented in Poland. The managed care programme (MCP) includes also the quality of care assessment based on clinical measures (e.g. cardiovascular risk factors control) as well as on the rate of minor and major cardiovascular events. The goal of the analysis was to assess the overall mortality of MI survivors participating and not participating in the MCP. Methods: The database of survivors of acute MI discharged from hospital from October 1, 2017 to December 31, 2018 was analyzed. Patients who died within 10 days after discharge were excluded from the analysis. The primary end-point was defined as death from any cause. Propensity-Score Matching (PSM) using nearest neighbor matching was used to form comparable groups of patients participating and not participating in the MCP. The Cox proportional hazard regression analysis was used to assess the relation between MCP and the overall mortality. Results: MCP was implemented in the first stage in 48 hospitals spread around the country (about 34% of all hospitals treating acute MI patients in Poland). Out of 87739 analyzed patients (age: 68.1±11.9 years; 55581 men and 32158 women) 34064 were hospitalized in hospitals with MCP implemented. Altogether 10404 patients (11.9% of the whole cohort; 30.5% of those hospitalized in hospitals with MCP implemented) participated in MCP. They were matched with 10404 patients not participating in the MCP. During 324.8±140.5 days of follow-up 7413 patients died. One-year mortality was lower in patients participating in the MCP both when we analyzed the whole cohort (4.4% vs. 9.5%; p<0.001) as well as when we limited the analysis to the PSM groups (4.4% vs. 6.5%; p<0.001, figure 1). MCP was related to the overall mortality in univariate (HR 0.43 [0.39–0.48]) as well as in multivariate analysis (0.64 [0.57–0.71]) in the whole cohort as well as in the PSM cohort (HR 0.63 [0.56–0.72] and 0.64 [0.56–0.72] for the univariate and multivariate analysis respectively). When we limited the analysis to hospitals in which MCP was implemented one-year mortality was 4.3% vs. 6.3% (p<0.001) whereas univariate HR was 0.51 (0.44–0.60) and multivariate HR 0.52 (0.44–0.61). Conclusion: The implemented in Poland nation-wide system of managed care for MI survivors is related to improved survival. Therefore, the Ministry of Health plans to implement the programme in all cardiac centers in Poland. Funding Acknowledgement: Type of funding source: None